Feasibility of cloud computing adoption in private hospital from security perspective - Nurbaini Zainuddin, 1977-, author; Nurazean Maarop, supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat)) - Universiti Teknologi Malaysia, 2015